2013
DOI: 10.1021/jp405430m
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Photoinjection of Hot Plasmonic Carriers from Metal Nanostructures into Semiconductors and Surface Molecules

Abstract: We investigate theoretically the effects of generation and injection of plasmonic carriers from an optically excited metal nanocrystal to a semiconductor contact or to surface molecules. The energy distributions of optically excited hot carriers are dramatically different in metal nanocrystals with large and small sizes. In large nanocrystals, the majority of hot carriers has very small excitation energies, and the excited-carrier distribution resembles the case of a plasmon wave in bulk. For nanocrystal sizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
623
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 529 publications
(647 citation statements)
references
References 59 publications
21
623
2
1
Order By: Relevance
“…Plasmonic metallic nanoparticles have an absorption cross-section much larger than the physical size of the particles [67], yielding much more efficient hot electron generation than bulk metal. Plasmonic nanoparticles also produce hot carriers at a higher average energy compared to absorption in bulk metals [30,31,68,69]. Lastly, the momentum distribution of hot carriers can be modified by engineering the modes of the plasmonic structures.…”
Section: Internal Photoemissionmentioning
confidence: 99%
See 3 more Smart Citations
“…Plasmonic metallic nanoparticles have an absorption cross-section much larger than the physical size of the particles [67], yielding much more efficient hot electron generation than bulk metal. Plasmonic nanoparticles also produce hot carriers at a higher average energy compared to absorption in bulk metals [30,31,68,69]. Lastly, the momentum distribution of hot carriers can be modified by engineering the modes of the plasmonic structures.…”
Section: Internal Photoemissionmentioning
confidence: 99%
“…This broad hot electron energy distribution sets an impediment for realizing high efficiency in the internal photoemission process, as many carriers will have an energy that is below the Schottky barrier [28]. In contrast to bulk metals, it has been shown that the hot carrier energy distribution in plasmonic nanoparticles can potentially be narrowband [30,31,69,71,72] and is strongly dependent on the particle size [30,69] and geometry [71,73,74] ( Figure 1D). For instance, hot carriers are more efficiently generated in small plasmonic nanoparticles compared to large ones [30].…”
Section: Hot Carrier Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…18,[23][24][25] To this end, metal-semiconductor (MS) Schottky junctions have been employed, 11,12,26 that take advantage of the built-in field in the vicinity of the metal nanostructure to separate the photogenerated carriers. The use of metalinsulator-metal architectures was also successfully employed for hot-electron photodetection.…”
Section: Introductionmentioning
confidence: 99%